Disturbance Induced Changes in Diversity of Medicinal Plants in a Dry Tropical Forest of India - Singh, Prasant Kumar; Prajapati, Santosh Kumar; Sunita, Kumari; Chaturvedi, Ravi Kant (Frontiers in Forests and Global Change, 2022)
Due to overexploitation for forest resources, many important medicinal plants are disappearing from the tropical dry forest (TDF) regions. The present study is aimed to investigate the diversity of medicinal plants exposed to different levels of anthropogenic disturbance in TDFs. For this study, we selected six forest regions, covering a radius of 25 km, and exposed to variable intensity of disturbances, in the form of illegal logging, cattle grazing and fire. Based on the intensity of three disturbances, we categorized the study sites as low (LDS) and high (HDS) disturbed sites, and analyzed differences in soil properties and vegetation parameters in the two disturbance categories. We recorded tree density, tree species richness and herbaceous species richness in 100 m2 quadrats at the selected regions. Results exhibited significantly greater soil organic C (LDS, 4.6%; HDS, 0.9%; P < 0.001), water holding capacity (LDS, 47.4%; HDS, 33.6%; P < 0.001), and sand content (LDS, 53.7%; HDS, 48.3%; P < 0.001) across low disturbed sites, whereas significantly higher bulk density (LDS, 1.30 gcm-3; HDS, 1.34 gcm-3; P < 0.05) and gravel content (LDS, 14.6%; HDS, 20.0%; P < 0.001) across high disturbed sites. We found considerable shift in relationships between vegetation parameters under the two disturbance regimes. The results indicated that many of the important medicinal plants (e.g., Adina cordifolia, Bauhinia vahlii, Holarrhena antidysenterica, Asparagus racemosus, Curculigo orchioides, Hemidesmus indicus, etc.) which are important constituents of several ayurvedic preparations as well as of traditional medical system are lacking from the high disturbed sites, either due to direct impact of disturbances or indirectly due to disturbance induced changes in soil properties. For instance, the high grazing pressure increased soil compaction, leading to increase in bulk density and decline in water holding capacity of soil. We suggest that forest managers take into consideration the presence of anthropogenic disturbances in their management and conservation efforts of medicinal plants in TDFs.